Almond milk production and study of quality characteristics / Nor Aishah Hasan - Hasan, Nor Aishah (Universiti Teknologi MARA, Negeri Sembilan, 2012)
Almond milk production at pilot plant and basic characterization were performed. The study included the effect of 0.03 % lecithin addition to the raw product and pasteurization (90 ºC, 15 s) with two step homogenization (180 MPa and 40 MPa), resulting in the comparison of four different almond milks: raw product (PB), raw product with lecithin (PBL), pasteurized product (PH) and pasteurized product with lecithin (PHL). Compositional characteristic of almond milks showed the proximate composition similar to those found in the market. The effect of lecithin addition is to improve product stability and these differences were observed at days 2 and 7 of storage at 4 oC and 25 oC. Total counts and Micrococcacceae were reduced by 2.21 and 3.64 log cycles at pasteurized almond milk while no viable Enterobacteriaceae nor yeast and mould remained in any pasteurized milk samples. Pasteurized almond milk inactivated lipoxygenase activity compared to untreated almond milk. The formations of oxidized substances (malondialdehyde and lipid hydroperoxides) in almond milk were all greatly reduced by pasteurization.